The lighthouse family. The storm / by Cynthia Rylant ; illustrated by Preston McDaniels. - Rylant, Cynthia (Simon & Schuster Books for Young Readers, 2002)
Pandora the cat becomes a lighthouse keeper and saves the life of Seabold the dog, and together the two of them create a family with three young mice rescued from the sea.